The development of Halal Hub Malaysia from Halal Industry Development Corporation (HDC) perspective : the qualitative approach in refining its implications and challenges / Nor Amira Najwa Nordin - Nordin, Nor Amira Najwa (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Halal is an important things to all Muslims and they must consume only lawful products and services. Halal hub which is a place that all good and services are in the same line with Syariah principles. All the Halal parks in Malaysia has created Halal hub and this is Malaysian government goal to make Malaysia as global Halal hub in 2020. This Halal parks has been manage by Halal Industry Development Corporation (HDC). This research provide enough knowledge regarding Halal hub, Halal industrial parks and HDC which is Muslims still clueless and less aware about it.